The Variety of Mathematics Learning Media for Early Childhood in Improving Basic Mathematics Ability - Rohibni, Rohibni; Rokhmawan, Tristan; Sayer, Inaad Mutlib; Fitriyah, Lailatul (Bulletin of Science Education, 2022)
Introduction to mathematics in early childhood is a very important cognitive aspect to be given. One of the things that can be done is the development of innovative mathematics learning media for early childhood. This study aims to conduct a literature review related to the various uses of mathematics learning media in early childhood. Data collection was carried out by reviewing all related articles published in the 2019-2022 period. After conducting a thorough review, there were 30 reputable articles from accredited journals used in this study. The results showed that there were 27 effective learning media that could be used by teachers at the time of learning to improve early childhood math skills. The researchers found that the teachers changed the normal learning strategy to a limited face-to-face learning strategy. For example in schools, teachers as educators had their own short-time learning strategies, so the learning process can be conducted effectively. Keywords: Online Learning, Application E-Learning, Web-Based E-Learning